(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the attention given to girls’ education in new-method schools established within the framework of the Jadid movement, the efforts made in this direction, and their results. It reveals the initiatives aimed at reinterpreting the role of women in Muslim society through the progressive ideas of the Jadids, focusing on shaping them as literate, well-mannered, and socially active individuals. Additionally, factors that hindered the activities of Jadid women’s schools - social resistance, religious conservatism, and financial problems - are also discussed.